Chromosome contribution to andean polyploid species of Senecio (Asteraceae), from Argentina - López, Mariana G. (2002)
Fil: López, Mariana G.. Lab. de Citogenética y Evol.; Depto. de Ciencias Biológicas; Universidad de Buenos Aires